2015
DOI: 10.1159/000437261
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Venous Thrombosis and Pulmonary Embolism by Combined CT Venography and Pulmonary Angiography in Patients with Cryptogenic Stroke and Patent Foramen Ovale

Abstract: Background: Paradoxical embolism via a patent foramen ovale (PFO) has been suggested as a potential stroke mechanism. Combined CT venography and pulmonary angiography (CVPA) is a simple, validated and accurate technique to diagnose deep venous thrombosis (DVT) or pulmonary embolism (PE). We sought to assess the prevalence of DVT or PE among patients with PFO and cryptogenic stroke (CS) by CVPA. Methods: Patients were identified retrospectively from a clinical registry of consecutive patients with stroke admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 15 publications
2
15
0
2
Order By: Relevance
“…In the present study, DVT was found in 29% of CS patients with an RLS. This is partially in concordance with previous research showing that 7-27% of CS patients with PFO had DVT (7)(8)(9)(10)(11)(12). The prevalence of DVT in CS patients with an RLS has varied widely because the rates of antithrombotic usage and the methods and timing of DVT evaluation differed among the previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, DVT was found in 29% of CS patients with an RLS. This is partially in concordance with previous research showing that 7-27% of CS patients with PFO had DVT (7)(8)(9)(10)(11)(12). The prevalence of DVT in CS patients with an RLS has varied widely because the rates of antithrombotic usage and the methods and timing of DVT evaluation differed among the previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Prevalence of venous thrombosis among cryptogenic stroke patients varies considerably (7.2-40%) and is highly dependent on the type of imaging modality. 25 Although noninvasive testing for paradoxical embolism include lower extremity doppler ultrasound that detects superficial or deep venous thrombi, the study is impeded by limited sensitivity and reliance on the skills of ultrasound technician. 26 Venous thrombi -formed in thrombogenic conditions− precedes a paradoxical embolism via PFO and results in small distal infarcts without any visible large vessel occlusion on angiography.…”
Section: Imaging Pattern For Paradoxical Embolismmentioning
confidence: 99%
“…Otras variables de riesgo han sido detectadas en estudios randomizados (tamaño amplio del FOP, ASIA, hipermovilidad del septum interauricular) (12,16) y en estudios retrospectivos (válvula de Eustaquio prominente, red de Chiari, túnel largo del FOP) (17) . Lógicamente, un tromboembolismo pulmonar reciente o concomitante, o una fuente venosa de embolia al mismo tiempo que el ictus, sugieren la participación del FOP en el escenario clínico (18) . Asimismo, es importante considerar la actividad que estaba realizando el paciente (maniobras de fuerza) y su contexto clínico (inmovilización, cirugía mayor reciente, viaje prolongado en automóvil o en avión) (6) .…”
Section: Probabilidad De Que El Foramen Oval Permeable Tenga Un Rol Runclassified